Efficient Defect Passivation and Charge Extraction with Hexamethylenetetramine Interface Modification for Hole‐Transporting Layers‐Free CsPbBr3 Perovskite Solar Cells. Issue 8 (8th July 2021) - Sun, Mingran; Zhu, Jingwei; He, Benlin; Bu, Fan; Ti, Junjie; Yao, Xinpeng; Chen, Haiyan; Duan, Yanyan; Tang, Qunwei
Abstract : The passivation of defects at perovskite films, surfaces and the promotion of charge extraction across perovskite/carbon back interface are of vital importance to develop the power conversion efficiency (PCE) and stability of carbon‐based perovskite solar cells (PSCs) free of hole‐transporting layers (HTLs). Herein, an electron donor material with polyamino groups, hexamethylenetetramine (HMTA), is used as an efficient surface modifier for tribrominated all‐inorganic perovskite films. The modification with HMTA not only eliminates the defects by forming a bond between N atoms and positively charged ions but also optimizes the energy level structure of the perovskite film and back interface contact. Therefore, CsPbBr3 films with decreased trap states, extended carrier lifetimes, and enhanced hole mobility are gained, which significantly restrains charge recombination and energy loss as well as facilitates charge extraction and transfer at the perovskite/carbon interface. Finally, an improvement of PCE from 6.75% to 10.08% is obtained for carbon‐based HTL‐free CsPbBr3 PSCs without and with HMTA modification, respectively. Furthermore, the HMTA‐modified device without encapsulation presents an enhanced long‐term moisture and heat stability after being stored in the atmospheric environment with 80% relative humidity (RH) at 25 °C and 20% RH at 85 °C, respectively, due to the reduced defects and the improved hydrophobicity of perovskite film. Abstract : The carbon‐based hole‐transporting layer (HTL)‐free CsPbBr3 perovskite solar cells (PSCs) achieve a maximum power conversion efficiency (PCE) of 10.08% with a high V OC of 1.605 V and an excellent stability through passivating defects and enhancing charge extraction by interface modification with hexamethylenetetramine (HMTA).